Ibsen in Dutch theatres and the sustainability of Nora - Janke Klok (Nordlit: Tidsskrift i litteratur og kultur, 2015)
In this article I reflect on Ibsen's laborious road to the Dutch stages to display the reciprocal influence between innovating theatre plays and the process of a modernizing society. In doing this I take into account insights from translation theory and the thinking on cultural mediation, whereby cultural transmission is seen as a way of interacting: the receiving culture’s receptivity towards new ideas and new forms is crucial for the space available for innovative literature from abroad. Tracking Ibsen on the Dutch stages shows a wavelike movement. Research into the reception of Ibsen supports the claim by the Dutch author Ina Boudier-Bakker (1875-1966) who used the late first staging of Ibsen's A Doll's House (1889) to illustrate the Amsterdam and Dutch conservatism with regard to gender roles and avant-garde art. Prior to 1890 the Netherlands lagged behind other European countries. With the Dutch production of A Doll’s House a new era arrives.After a flying start and a growing appreciation for Ibsen as a social reformer, particularly concerning entrenched (gender) conventions, Dutch critics in the period 1930-1970, do not seem to be able to place Ibsen’s plays. A qualitative analysis of the revival by way of the jubilee performance Ghosts in 1956, shows that Dutch audiences hold off a contemporary debate by focusing on geographical and ethnographical distance. It indicates that in the fifties this audience was intellectually and artistically conservative. Tracking Ibsen on the stages after 1970 shows us the current multicultural society; it shows us a renewed interest in his female characters, which culminates with Nora. It shows us an increasing number of women directors in Dutch theatres, also in advanced theatre school performances. Present-day Dutch theatres and their audiences seem to be mostly interested in Ibsen’s theatre women, be it his female characters or the relatively new phenomenon of women directing his plays. Their experiments with his texts are highly appreciated and show a renewed interest in public debate, re-establishing the discussion that was aroused in the first period of staging Ibsen in the Netherlands. The experiments with Ibsen’s “old” female characters by his “new” women directors form a most important ingredient of his modernity and sustainability, both where content (feminism = noraism) and where form are concerned. It is these women who confirm Ibsen’s position as an author of today’s world.